Evaluation of hysterectomy in a tertiary care hospital of central India: a retroprospective study - Mahilange, Anchala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hysterectomy is the most common gynaecological surgical procedure after caesarean section. In India there is lower rate (4-6%) of hysterectomy has been reported, while there is higher frequency of hysterectomy (10-20%) in developed countries. Currently there are three main types of hysterectomy operations in practice for benign diseases abdominal hysterectomy, vaginal hysterectomy and laparoscopic hysterectomy. Abdominal hysterectomy remains the predominant method of uterus removal. The present study was planned t to analyse changes in the trends of hysterectomy from past 3 year in the study area. Methods: The present observational study was conducted in department of obstetrics and gynaecology and associated Dr. B.R.A.M. hospital Raipur (CG), India. Data was collected retrospectively from January 2009 to May 2012 from hospital medical records. Prospectively data was obtained from patient and his file from June 2013 to September 2014. Data was compiled in MS-excel and checked for its completeness and correctness, and then it was analyzed by using suitable software. Results: Total no of hysterectomy conducted in study duration was 1000. Study showed declining trend of hysterectomy in our institute. Most common age group of hysterectomy was 41-50 year. which 45.8% followed by age group 31-40 that is 32.5%. Most common indication of hysterectomy was fibroid uterus 33.6% followed by prolapse uterus 29.5%. 29% cases were operated via vaginal route for descent of uterus and 21% cases operated by vaginal route for non-descent uterus.50% cases were operated via abdominal route. Average operating time for TAH was 1.43±0.50, for VH was 1.08±0.03. Average hospital stay for TAH was 8.87±3.31 and VH was 5.27±1.07. Conclusions: In our study it had been seen that rate of hysterectomy is in decreasing trend as more conservative approach is now preferred. To minimize most of complications of hysterectomy second opinion fresh eyes and multi-disciplinary approach is recommend in all patients undergoing this procedure.